2015
DOI: 10.15252/msb.20145844
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback buffers effects of regulatory variants

Abstract: Mechanisms conferring robustness against regulatory variants have been controversial. Previous studies suggested widespread buffering of RNA misexpression on protein levels during translation. We do not find evidence that translational buffering is common. Instead, we find extensive buffering at the level of RNA expression, exerted through negative feedback regulation acting in trans, which reduces the effect of regulatory variants on gene expression. Our approach is based on a novel experimental design in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
(105 reference statements)
6
28
1
Order By: Relevance
“…Nonetheless, our experiment had surprisingly strong power to detect cis effects. We found that >47% (7699) of gene expression patterns were affected by cis factors, a finding that exceeded other published studies using linear modeling to test for cis effects, which ranged from 15% to 30% (Cubillos et al 2014;Bader et al 2015). The increased power is likely attributable to significant genomic divergence between the parents and individual, rather than pooled, sequencing of each biological replicate (Liu et al 2014).…”
Section: Inference Of Cis-and Cis-treatment Gene Expression G×e Via Acontrasting
confidence: 50%
See 2 more Smart Citations
“…Nonetheless, our experiment had surprisingly strong power to detect cis effects. We found that >47% (7699) of gene expression patterns were affected by cis factors, a finding that exceeded other published studies using linear modeling to test for cis effects, which ranged from 15% to 30% (Cubillos et al 2014;Bader et al 2015). The increased power is likely attributable to significant genomic divergence between the parents and individual, rather than pooled, sequencing of each biological replicate (Liu et al 2014).…”
Section: Inference Of Cis-and Cis-treatment Gene Expression G×e Via Acontrasting
confidence: 50%
“…3; Bader et al 2015). We estimated that the expression of 5969 (π 0 = 0.63) of the 16,465 genes with quantifiable ASE were affected by trans factors; however, in many cases the trans effect size was relatively small (Fig.…”
Section: Trans and Trans-by-treatment Expression Regulatory Divergencementioning
confidence: 99%
See 1 more Smart Citation
“…GRN robustness has been explicitly formulated to account for the prevalence of compensatory cis-trans interactions (Denby et al 2012;Bader et al 2015). Denby et al (2012) have proposed that negative feedback controlling the level of RNA expression could be a common mechanism to buffer effects of regulatory variants in yeast.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated for a single gene that negative feedback could act as a buffering mechanism for regulatory variants. Bader et al (2015) quantified buffering by feedback against naturally occurring regulatory variants genome-wide to be 15%. Note that when buffering arises from feedback, it is not necessary to invoke additional genetic variation across the genome to explain the trans-effects.…”
Section: Discussionmentioning
confidence: 99%